Effect of soybean ureases on seed germination and plant development - Rechenmacher, Ciliana (Genet Mol Biol, 2017)
Urease catalyzes the hydrolysis of urea to ammonia and carbon dioxide. The ammonia (nitrogen (N) product of urease activity) is incorporated into organic compounds. Thus, urease is involved in N remobilization, as well as in primary N assimilation. Two urease isoforms have been described for soybean: the embryo-specific, encoded by the Eu1 gene, and the ubiquitous urease, encoded by Eu4. A third urease-encoding gene was recently identified, designated Eu5, which encodes the putative protein product SBU-III. The present study aimed to evaluate the contribution of soybean ureases to seed germination and plant development. Analyses were performed using Eu1/Eu4/Eu5-co-suppressed transgenic plants and mutants of the Eu1 and Eu4 urease structural genes, as well as a urease-null mutant (eu3-a) that activates neither the ubiquitous nor embryo-specific ureases. The co-suppressed plants presented a developmental delay during the first month after germination; shoots and roots were significantly smaller and lighter. Slower development was observed for the double eu1-a/eu4-a mutant and the eu3-a single mutant. The N content in transgenic plants was significantly lower than in non-transgenic plants. Among the mutants, eu3-a presented the lowest and eu1-a the highest N content. Altogether, these results indicate that increased ureolytic activity plays an important role in plant development.